Type of sexual intercourse experience and suicidal ideation, plans, and attempts among youths: a cross-sectional study in South Korea - Kim, Geum Hee (BMC Public Health, 2016)
BACKGROUND: Despite abundant theoretical evidence of higher rates of suicide among lesbian, gay, and bisexual (LGB) youths, little is known about the relationship between suicide and types of sexual intercourse experience in youths. This study examines the association between the type of intercourse experience and suicide risk outcomes (SROs: suicidal ideation, plans for suicide, suicidal attempts) from the Korea Youth Risk Behavior Web-based Survey. METHODS: We analyzed cross-sectional data from 146,621 students aged 12–17 years for the years 2012 and 2013. We defined lesbian, gay, or bisexual youth as youths who engaged in a type of sexual intercourse (same-sex or both-sex intercourse). A chi-square test and logistic regression analysis were used to evaluate the association between intercourse experience and SROs. RESULTS: The results showed that the prevalence of suicidal ideation was higher among youths with same-sex intercourse experience (45.9% for females, 33.7% for males) than among youths with opposite-sex intercourse experience (42.2% for females, 23.8% for males) and those with no experience in intercourse (21.0% for females, 12.7% for males). After adjusting for revealed risk factors that were associated with suicide risks, among males, suicide risks based on intercourse experience seemed to increase in the following order: no experience in sexual intercourse, opposite-sex, same-sex, and then both-sexes sexual intercourse experience. Same- and both-sexes intercourse related SROs are strongly linked to violence (being physically assaulted, threatened, or bullied) and sexually transmitted diseases (STDs), including HIV infection. Those having no sexual intercourse experience showed the least probability of suicide risks among youths. CONCLUSION: The SROs of youths with same-sex or both-sex intercourse experience had strong associations with gender (males), violence, and STDs. Therefore, school educators must continue to advocate for and to implement LGB inclusive policies and programs in order to promote safe and supportive learning environments where all students are protected from health risk behaviors.